Is Evictionism a Solution to the Abortion Problem? - Szutta, Artur (Roczniki Filozoficzne, 2025)
This paper critically evaluates the libertarian theory of evictionism as a proposed solution to the moral and legal problem of abortion. Evictionism, defended by Walter Block, attempts to reconcile pro-life and pro-choice intuitions by distinguishing between eviction (removal of the fetus) and killing, grounding the permissibility of abortion in absolute property rights and bodily autonomy. The paper systematically examines Block’s defence of evictionism, addressing key claims such as those about the status of the fetus as a trespasser, the absoluteness of property rights, and the acceptability of lethal eviction in early pregnancy. Drawing on thought experiments and the principle of proportionality, I argue that evictionism fails to account for moral responsibility toward dependent beings and leads to ethically implausible conclusions. Furthermore, I show that evictionism contradicts the proviso Block himself accepts, ultimately concluding that the theory is internally inconsistent.